2018
DOI: 10.1016/j.ijnurstu.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Associations between nurse education and experience and the risk of mortality and adverse events in acute care hospitals: A systematic review of observational studies

Abstract: While evidence suggests that higher nurse education is associated with lower risks of mortality and failure to rescue, longitudinal studies are needed to better ascertain these associations and determine the specific thresholds that minimize risks. Further studies are needed to better document the association of nurse education and experience with other nursing-sensitive adverse events, as well as the benefits to patients and organizations of the Institute of Medicine's recommendation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
139
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(153 citation statements)
references
References 60 publications
2
139
0
3
Order By: Relevance
“…However, safe staff nursing also covers their competencies, that is the skills, knowledge, abilities and personal attributes necessary for the delivery of effective and high‐quality care, in addition to the number of nurses available (Freitas & Parreira, ; Freitas et al, ). Evidence suggests that nurse competencies/education is associated with patient safety (Audet et al, ; Griffiths et al, ), and this association is also highlighted in the results of the path analysis.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, safe staff nursing also covers their competencies, that is the skills, knowledge, abilities and personal attributes necessary for the delivery of effective and high‐quality care, in addition to the number of nurses available (Freitas & Parreira, ; Freitas et al, ). Evidence suggests that nurse competencies/education is associated with patient safety (Audet et al, ; Griffiths et al, ), and this association is also highlighted in the results of the path analysis.…”
Section: Discussionmentioning
confidence: 83%
“…However, despite the scientific evidence that nurse staffing is a determinant of health outcomes (Aiken et al, ; Audet, Bourgault, & Rochefort, ), there is an inadequate staffing, as a result of austerity measures. This is particularly worrying in Portugal, because the number of nurses per 1,000 inhabitants (6.38 nurses per 1,000 inhabitants) is below the European average (8.64 nurses per 1,000 inhabitants) and is one of the lowest ratios in OECD countries (Simões, Augusto, Fronteira, & Hernández‐Quevedo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nursing professional education could upgrade clinical performance (Audet et al, ) and patient safety (Jessie et al, ). In the sense that nursing professional education could enhance professional capabilities, the present study is new in indicating novel impacts of nursing professional education, that is, reducing professional turnover intention.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that higher education is known to foster greater cognitive skills and is linked to improved patient outcomes . In well‐renowned research on nursing education and skill mix , Aiken et al.…”
Section: Discussionmentioning
confidence: 99%